2017
DOI: 10.1016/j.jsat.2017.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Marijuana use and HIV treatment outcomes among PWH receiving care at an urban HIV clinic

Abstract: Background While marijuana use is prevalent among persons with HIV (PWH), few studies have examined the relationship between marijuana use and HIV treatment outcomes independent of alcohol and other drug use. Methods We conducted a prospective cohort study to examine the relationships between frequency of marijuana use and antiretroviral therapy (ART) adherence and viral suppression in patients enrolled in the Johns Hopkins HIV Clinical Cohort between September 2013 through November 2015 (N=1377). We categor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 33 publications
2
14
0
Order By: Relevance
“…Recent metaanalyses have indicated that single-session interventions are crucial for reducing HIV transmission and ideal for implementation in resource-deprived environments (Diallo et al, 2010;Eaton et al, 2012;Sagherian et al, 2016); they have also shown promising results in improving adherence among individuals with adherence problems (Safren et al, 2001). Similar to previous research on ART adherence, our findings suggest that marijuana usage does not prevent HIV-infected individuals from adhering to their ART regimen (Mimiaga et al, 2013;Sinha et al, 2017). Instead, recent marijuana use was associated with VL reduction over the previous 3 months, which may indicate that participants were using marijuana for therapeutic or medicinal purposes, which has been observed in previous studies on drug use among HIV-infected individuals (de Jong et al, 2005;D'Souza et al, 2012).…”
Section: Discussionsupporting
confidence: 86%
“…Recent metaanalyses have indicated that single-session interventions are crucial for reducing HIV transmission and ideal for implementation in resource-deprived environments (Diallo et al, 2010;Eaton et al, 2012;Sagherian et al, 2016); they have also shown promising results in improving adherence among individuals with adherence problems (Safren et al, 2001). Similar to previous research on ART adherence, our findings suggest that marijuana usage does not prevent HIV-infected individuals from adhering to their ART regimen (Mimiaga et al, 2013;Sinha et al, 2017). Instead, recent marijuana use was associated with VL reduction over the previous 3 months, which may indicate that participants were using marijuana for therapeutic or medicinal purposes, which has been observed in previous studies on drug use among HIV-infected individuals (de Jong et al, 2005;D'Souza et al, 2012).…”
Section: Discussionsupporting
confidence: 86%
“…"g" is gram. "ml" is milliliter earlier research done in other countries, which showed approximately 25% used alcohol in Africa and 21.8% in the United States in previous month [16,17]. Evidence has shown that the health outcomes are worse in patients who often drink alcohol, including a higher incidence of psychosocial problems and lower treatment adherence levels [18][19][20][21][22].…”
Section: Discussionmentioning
confidence: 97%
“…57 In contrast to alcohol and club drug use, recent evidence suggests no link between marijuana use and HIV medication non-adherence. 58,59 Nonetheless, further study is needed with PrEP users who use marijuana because of the varying contextual situations in which anti-retrovirals are used (i.e., for sustained health among people living with HIV compared to HIV prevention among PrEP users), which could result in differential adherence patterns.…”
Section: Introductionmentioning
confidence: 99%